Study of cosmic ray composition in the knee region using multiple muon events in the Soudan 2 detector - Kasahara, S; Allison, W; Alner, G; Ayers, D; Barrett, W; Bode, C; Border, P; Brooks, C; Cobb, J; Cockerill, D; Cotton, R; Courant, H; et al. (1997)
Deep underground muon events recorded by the Soudan 2 detector, located at a depth of 2100 m of water equivalent, have been used to infer the nuclear composition of cosmic rays in the "knee" region of the cosmic ray energy spectrum. The observed muon multiplicity distribution favors a composition model with a substantial proton content in the energy region 8 × 105-1.3×107 GeV/nucleus.